1999
DOI: 10.1177/026988119901300109
|View full text |Cite
|
Sign up to set email alerts
|

The safety and tolerability of zolpidem — an update

Abstract: Zolpidem belongs to a new class of hypnotic agents, chemically distinct from the pre-existing ones, and has a unique neuropharmacological profile. It induces sedative/hypnotic effects in rodents at doses much lower than those for anticonvulsant and myorelaxant activities. Clinically, zolpidem is indicated for the short term treatment of insomnia. It has a short half-life (2.4h), with no active metabolite, and does not accumulate during repeated administration. The pharmacokinetic profile associated with the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(76 citation statements)
references
References 87 publications
3
72
0
1
Order By: Relevance
“…The GABA A receptor a1 subunit-preferring BZ-site ligand ZOL has less abuse liability than DZ (Darcourt et al, 1999;Hajak et al, 2003;Griffiths and Johnson, 2005). Here we found that ZOL at the dose (5 mg/kg) that acts specifically via a1 subunit-containing receptors (Crestani et al, 2000) increased the AMPA/NMDA ratio in VTA DA neurons.…”
Section: Discussionmentioning
confidence: 99%
“…The GABA A receptor a1 subunit-preferring BZ-site ligand ZOL has less abuse liability than DZ (Darcourt et al, 1999;Hajak et al, 2003;Griffiths and Johnson, 2005). Here we found that ZOL at the dose (5 mg/kg) that acts specifically via a1 subunit-containing receptors (Crestani et al, 2000) increased the AMPA/NMDA ratio in VTA DA neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Zolpidem is recommended for the reduction of sleep onset time, increase total duration of sleep and sleep efficiency, given in doses of 5 up to 7.5 mg [1,6] for the short-term treatment of insomnia [7].…”
Section: Introductionmentioning
confidence: 99%
“…Is characterized by linear kinetics in the 5-20 mg dose range [5], is highly bound to plasma proteins (around 92%) [6] and it is subjected to extensive hepatic metabolism [7,8]. Zolpidem is a substrate to several distinct CYP 450 isoenzymes, among which the major metabolism pathway occurs through CYP3A4 (61%) [9,10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Although ZLP appears to be well-tolerated in adults and the elderly [4], there is a host of reports of its abuse, dependence and withdrawal syndrome. It is worth mentioning that in the majority of these reported cases, the recommended dose of ZLP is exceeded and most of the patients have a history of substance How to cite this paper: Parsa, A., Mohammadkhan, A. and Babaeian, M. (2017) Zolpidem-Induced Narcolepsy, Faint, Seizu-abuse and/or psychiatric disorder [5] [6].…”
Section: Introductionmentioning
confidence: 99%